A microfabricated semi-packed column coated with porous layer and ionic liquid for the separation of characteristic markers of non-alcoholic fatty liver disease. (1st August 2022) - Shi, Lujia; Wang, Hairong; Wu, Xinyu; Wang, Dazuo; Zhang, Qunming; Han, Baoqing; Sun, Jianhai; Wei, Xueyong; Li, Changqing
Abstract: A serpentine-shaped semi-packed micro gas chromatography (GC) column with mesoporous inner surface and ionic liquid (IL) coating was developed for the separation of various typical volatile organic compounds in exhaled air. The mesoporous surface was prepared by coating silica nanoparticles on the inner surface of the micro GC column through static method and used as stationary phase support to improve the separation performance by its high surface area. The micro GC columns provide efficient separations for analytes including nonpolar (alkanes), weak polar (benzene series) and polar compounds (alcohols), as well as various typical markers of non-alcoholic fatty liver disease. The test results show that the resolution of most analytes is higher than 1.5, the elution peaks are symmetrical. Moreover, due to the chemical stability of IL, the micro GC had good repeatability, thermal stability and oxygen robustness. The maximum relative standard deviation of retention time was 0.44% in four weeks. During the programmed heating, a stable baseline was achieved and the baseline drift value was less than 4.8 mV when the operating temperature increased from 50 °C to 140 °C. The oxygen robustness was verified by a decrease of 7.2% in the peak capacity after exposure to dry air at 140 °C for 48 h. These characteristics showed the micro GC column is suitable for a portable breath analyzer.